Cerita Ratu Tribhuwana Wijayatunggadewi Sebagai Sumber Ide Perancangan Motif Batik Majapahit - Rismawati, Aristya Rizky Rismawati; Indarti, Indarti (Practice of Fashion and Textile Education Journal, 2024)
Queen Tribhuwana Wijayatunggadewi was one of the leading female rulers and playeda significant role in organizing and expanding Majapahit's territory. This research aimsto find out 1) the process of designing Majapahit batik motifs with the source of ideasfrom the story of Ratu Tribhuwana Wijayatunggadewi, 2) the resulting Majapahit batikmotifs with the source of ideas from Queen Tribhuwana Wijayatunggadewi. The methodused is the Double Diamond Model which consists of 4 stages, namely discover, define,develop and deliver. In the initial stage, summarize the sources of ideas to create amoodboard with a predetermined theme which leads to batik motif designs. The secondstage is developing a moodboard that has been made into several stylizations. The thirdstage is arranging the stylization into 6 batik motif developments. The fourth stage is theprocess of producing a prototype of one of the Majapahit batik designs with the sourceof the idea being Queen Tribhuwana Wijayatunggadewi. This research produced 6 batikmotif designs for the story of Queen Tribhuwana Wijayatunggadewi, and of these 6designs, 1 design was selected which was realized in the form of batik cloth with the storymotif of Queen Tribhuwana Wijayatunggadewi with a cloth size of 200 x 115 cm.